The relationship of store design and location a case study of Cinderella specialty stores - Javier, Kristine G.; Mayo, Adelaida Villaraza (1998.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman
Keywords: Cinderella Specialty Stores; Store decoration -- Philippines